2015
DOI: 10.1556/2006.4.2015.039
|View full text |Cite
|
Sign up to set email alerts
|

Think twice: Impulsivity and decision making in obsessive–compulsive disorder

Abstract: Background and AimsRecent studies have challenged the anxiety-avoidance model of obsessive–compulsive disorder (OCD), linking OCD to impulsivity, risky-decision-making and reward-system dysfunction, which can also be found in addiction and might support the conceptualization of OCD as a behavioral addiction. Here, we conducted an exploratory investigation of the behavioral addiction model of OCD by assessing whether OCD patients are more impulsive, have impaired decision-making, and biased probabilistic reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 70 publications
5
106
0
2
Order By: Relevance
“…This is important because a link between changes in reward systems, impulsivity and psychiatric disorders including OCD has been convincingly documented (Eslami-Shahrbabaki et al, 2015; Grassi et al, 2015). An important implication of the quinpirole sensitization in relation to neurobiology is a proposal that OCD as a clinical condition can represent a disorder of a “security motivation” system (Szechtman and Woody, 2004).…”
Section: Construct Validity Of the Qsmmentioning
confidence: 99%
“…This is important because a link between changes in reward systems, impulsivity and psychiatric disorders including OCD has been convincingly documented (Eslami-Shahrbabaki et al, 2015; Grassi et al, 2015). An important implication of the quinpirole sensitization in relation to neurobiology is a proposal that OCD as a clinical condition can represent a disorder of a “security motivation” system (Szechtman and Woody, 2004).…”
Section: Construct Validity Of the Qsmmentioning
confidence: 99%
“…It is a necessary ability for adequate functioning, and is often impaired in patients with psychiatric disorders such as schizophrenia, 1 obsessive-compulsive disorder, 2,3 bipolar disorder (BD) 4 and depression, 5 and neurological disorders such as multiple sclerosis 6 and traumatic brain injury. 7 Recent studies have also identified it as a significant predictor of clinical outcomes such as treatment dropout and relapse in substance disorders 8,9 and future substance use in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, choosing the probabilistic reinforcer is advantageous. Regardless, risky decision making is associated with attention deficit/hyperactivity disorder (ADHD; see Dekkers et al, 2016 for a meta-analysis), borderline personality disorder (Schuermann et al, 2011; Svaldi et al, 2012), human immunodeficiency virus (HIV; Fujiwara et al, 2015; Hardy et al, 2006), obsessive-compulsive disorder (OCD; Grassi et al, 2015), psychopathy (Takahashi et al, 2014), sleep deprivation (Killgore et al, 2006), substance abuse (Brevers et al, 2014; Schutter et al, 2011), and pathological gambling (PG; Brand et al, 2005; Madden et al, 2009). Directly related to probability discounting, individuals diagnosed with psychopathy and PG often show shallower discounting of a large, uncertain reinforcer relative to matched controls (Madden et al, 2009; Takahashi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%